2009
DOI: 10.1111/j.1872-034x.2009.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and liver tissue levels of retinol‐binding protein‐4 in non‐alcoholic fatty liver disease

Abstract: In NAFLD patients, serum RBP4 was significantly lower as compared with controls and did not correlate with insulin resistance. In contrast, RBP4 liver tissue expression was enhanced and correlated with NAFLD histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 33 publications
5
43
0
3
Order By: Relevance
“…This discrepancy may be due to the analysis of RBP4 expression in different adipose tissues: visceral adipose tissue in this study while subcutaneous adipose tissue in the human patients' study. Surprisingly, we did not find a change of RBP4 expression in the liver in response to either high fat diet or pioglitazone treatment, although RBP4 is abundantly expressed in the liver and secreted into the circulation in a 1:1:1 complex with retinol (holo-RBP4) and transthyretin [26]. This finding from the in vivo tissues was confirmed by the in vitro cell culture experiment wherein pioglitazone inhibited RBP4 expression only in adipocytes, but not hepatocytes.…”
Section: Discussionsupporting
confidence: 68%
“…This discrepancy may be due to the analysis of RBP4 expression in different adipose tissues: visceral adipose tissue in this study while subcutaneous adipose tissue in the human patients' study. Surprisingly, we did not find a change of RBP4 expression in the liver in response to either high fat diet or pioglitazone treatment, although RBP4 is abundantly expressed in the liver and secreted into the circulation in a 1:1:1 complex with retinol (holo-RBP4) and transthyretin [26]. This finding from the in vivo tissues was confirmed by the in vitro cell culture experiment wherein pioglitazone inhibited RBP4 expression only in adipocytes, but not hepatocytes.…”
Section: Discussionsupporting
confidence: 68%
“…It is notable that our findings were in accordance with observations from previous studies [14][15][16][17][18][19][20], which demonstrated that serum RBP4 levels were lower in patients with chronic liver diseases and the levels decreased as the diseases progressed to more severe stages. Nevertheless, recent investigations have shown that serum RBP4 levels are higher in patients with non-alcoholic fatty liver disease and chronic hepatitis C and these levels increase with the degree of liver steatosis [12,13].…”
Section: Discussionsupporting
confidence: 95%
“…Both animal and human studies have shown that RBP4 might be involved in the development of insulin resistance and diabetes [10,11]. Serum levels of RBP4 have been previously shown to be associated with the degree of steatosis and fibrosis in liver diseases of various etiologies, such as non-alcoholic fatty liver disease and chronic hepatitis C [12][13][14][15][16][17][18][19][20]. However, the precise mechanism of RBP4 influence on liver fibrogenesis is not clearly understood.…”
Section: Introductionmentioning
confidence: 97%
“…Circulating rbp4 has been shown to correlate positively with nonalcoholic fat liver disease in some studies, 17,18 but not others. 27,28 However, most of those studies have been performed in limited numbers of subjects. Our study, performed in a large population of patients with T2DM using a precise evaluation of liver fat content by proton magnetic resonance spectroscopy, does not find any significant association between plasma rbp4 and liver fat content.…”
Section: Discussionmentioning
confidence: 99%